Cash Holdings Decisions and Firm Size: Liquidity As A Moderator - Ulfida, Deafatunnizwa; Rizka, Nor Rahma (Universitas Pamulang, 2025)
This study delves into the influence of company size on cash reserves, leveraging liquidity as a moderating factor, particularly focusing on firms within the LQ45 index on the Indonesia Stock Exchange. The research employs a purposive sampling method, selecting companies meeting specific criteria such as continuous listing in the LQ45 index from 2021 to 2023 and consistent publication of comprehensive financial statements during this timeframe. The study encompasses 78 data points, aiming to shed light on the correlation between company size and cash reserves while emphasizing the moderating impact of liquidity within Indonesia's financial market landscape. The results are expected to provide valuable insights into the connection between firm size and cash holdings, while highlighting the moderating role of liquidity within Indonesia’s capital market context. This study contributes to the general knowledge of corporate finance by offering an empirical foundation for decision-making among stakeholders in the LQ45-listed firms.